Sex-specific differences in biomechanics among runners: A systematic review with meta-analysis - Xie, Ping-Ping; István, Bíró; Liang, Minjun (Frontiers in Physiology, 2022)
Patellofemoral disorders in female runners are more common in comparison with their male counterparts. The difference in biomechanical characteristics between female and male runners could provide the relative evidence for higher injuries rate happen in female runners, would be beneficial for physical therapists, athletic trainers to develop the individual’s prevention program. This review aimed at comparing biomechanical characteristics between female and male runners. Four electronic databases were searched. Crossover design studies comparing gender differences in lower extremity mechanics during running in healthy participants and written in English were involved. Mate-analyses were used where possible. 10 studies were selected. The difference of kinetic variables and muscle activation between females and males cannot be conducted a meta-analysis due to the insufficient data. The meta-analyses of kinematic variables, revealed that females exhibited significantly greater hip adduction angle, hip internal rotation angle, as well as keen flexion angle than males during running. There are significant differences in kinematic variables between female and male runners during running. Physical therapists, athletic trainers who work with running should be aware of these characteristics to develop injuries prevention programs and provide training advice.